Pengaruh pengetahuan aktual dan obyektif terhadap persepsi risiko pengunjung di Taman Hutan Raya Ir. H. Djuanda - Khairunisa, Reiqa; Rahmafitria, Fitri (Journal of Youth and Outdoor Activities, 2024)
Background: This research aims to examine the simultaneous influence of actual and objective knowledge on risk perception. Methods: This study uses a quantitative approach and descriptive methods to present an objective and precise picture of the variables being studied. The population selected in this study includes all domestic tourists visiting the Ir. H. Djuanda Forest Park. Conclusion: The results of the study show that actual and objective knowledge simultaneously have a significant influence on visitors' risk perception. Findings: This finding suggests that the combination of direct experience (actual knowledge) and factual information (objective knowledge) has a significant impact on visitors' risk perception, allowing them to assess risk more accurately and informatively.